2015
DOI: 10.1016/j.cmet.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

ATP Citrate Lyase Improves Mitochondrial Function in Skeletal Muscle

Abstract: Mitochondrial dysfunction is associated with skeletal muscle pathology, including cachexia, sarcopenia, and the muscular dystrophies. ATP citrate lyase (ACL) is a cytosolic enzyme that catalyzes mitochondria-derived citrate into oxaloacetate and acetyl-CoA. Here we report that activation of ACL in skeletal muscle results in improved mitochondrial function. IGF1 induces activation of ACL in an AKT-dependent fashion. This results in an increase in cardiolipin, thus increasing critical mitochondrial complexes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 37 publications
5
74
0
1
Order By: Relevance
“…Skeletal muscle ATP citrate lyase appears to orchestrate a coordinated response to elevate mitochondrial CL synthesis, as muscle-specific overexpression of this enzyme results in increased abundance and activities of ETS complexes [47]. However, the effect of CL to improve mitochondrial function is likely limited to mature CL.…”
Section: Cardiolipinmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle ATP citrate lyase appears to orchestrate a coordinated response to elevate mitochondrial CL synthesis, as muscle-specific overexpression of this enzyme results in increased abundance and activities of ETS complexes [47]. However, the effect of CL to improve mitochondrial function is likely limited to mature CL.…”
Section: Cardiolipinmentioning
confidence: 99%
“…Because CL is mostly unique to mitochondria, abundance of this molecule has been used as a marker for mitochondrial density. Indeed, total CL content increases with exercise training in rodents and in humans [47, 66]. Intriguingly, time-course experiments suggest that while CL content and ETS enzyme activity increase synchronously in response to exercise training, detraining promotes a decrease in total CL content that precedes a decrease in ETS enzyme activity [67].…”
Section: Exercise/inactivity and Skeletal Muscle Mitochondrial Phosphmentioning
confidence: 99%
“…The development of sarcopenia is not, however, solely an issue of impaired mitochondrial biogenesis (Argiles et al, 2015). Recently, it was also shown that phosphorylation and hence activity of ATP citrate lyase (ACL) a key regulator of acetyl-CoA levels, was markedly reduced in sarcopenic muscle (Das et al, 2015). In this study, ACL phosphorylation was stimulated by IGF-1, a growth factor known to increase muscle mass (Egerman and Glass, 2014), and also known to decline in the serum of aging men and woman (O'Connor et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, ACL phosphorylation was stimulated by IGF-1, a growth factor known to increase muscle mass (Egerman and Glass, 2014), and also known to decline in the serum of aging men and woman (O'Connor et al, 1998). Increasing ACL levels in mice resulted in improved mitochondrial function suggesting that this might be a complementary approach to combat the deleterious effects of skeletal muscle aging (Das et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…We next investigated the impact of CUL3 on de novo lipid synthesis by measuring the incorporation of 14 C-glucose into total lipids in cells, which is a widely used method to measure the rate of de novo lipid synthesis in cells Daemen et al 2015;Das et al 2015). Ectopic expression of Myc-CUL3 greatly inhibited de novo lipid synthesis in different cells (Fig.…”
Section: Cul3 Inhibits De Novo Lipid Synthesis Through Negative Regulmentioning
confidence: 99%